A Case of Bernard-Soulier Syndrome Associated with 22q11.2 Deletion Syndrome - Oh Cheol Kwon; Su Hyun Yoon; Sung Han Kang; Hyery Kim; Kyung-Nam Koh; Ho Joon Im (The Korean Society of Pediatric Hematology-Oncology, 2023)
22q11.2 deletion syndrome (22q11.2DS) is a disorder caused by microdeletions in the long arm of chromosome 22. It is one of the most common chromosomal microdeletion disorders. Clinical symptoms are caused by heterozygous deletion of chromosome 22q11.2 and include congenital heart diseases and palatal abnormalities. Bernard-Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder caused by deficiency of the glycoprotein Ib-IX-V complex (GPIb-IX-V), the receptor for von Willebrand factor. Glycoprotein Ib-beta (GPIbβ) gene mutation is one of the causes of BSS, and the GP1bβ gene is located on chromosome 22q11.2. Most 22q11DS patients do not have a bleeding issue since most of them have heterozygous deletion of the GPIbβ gene. However, we report a case in which a child with 22q11.2DS visited the hospital with subgaleal hemorrhage and was diagnosed with Bernard-Soulier syndrome with GPIbβ gene mutation by a platelet aggregation test and genetic sequencing.